Developing health-saving competence of pre-service teachers in Kazakhstan - Alibi Laulanbekov; Jamilya Torybayeva; Mukhamejan Tusseyev (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study's significance lies in the need for a perspective teacher who can solve educational objectives to preserve children's and teenagers’ health. In this context, it is crucial to cultivate the health-saving competence of pre-service teachers during the educational process at the university. The study has aimed to develop, implement and experimentally test educational conditions for developing health-saving competence of a pre-service teacher within the framework of the educational program of the pedagogical direction. The participants were 37 university teachers of physical education and 145 students from two universities in Kazakhstan. The proposed approaches and methods represent a process of future teacher training which includes the stages: initial, main and final. Instructional intervention was employed at the final stage: the authors developed and introduced a special course for prospective teachers titled "Development of Schoolchildren's Health and Modern Health-promoting Technologies”. Tests, surveys, and questionnaires have been used during the intervention to test the course efficiency. The majority of respondents (79%) consider it necessary to utilize health-promoting methods and techniques at different stages of the lesson in the process of teaching the discipline. The essential aspect in the study of the elective course was building upon students' existing knowledge in the fields of physical education, pedagogy, psychology, and subject-specific teaching methods, as well as enhancing their health-saving competencies.